3(x+y)-2(2y+x)+y=

Simple and best practice solution for 3(x+y)-2(2y+x)+y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+y)-2(2y+x)+y= equation:


Simplifying
3(x + y) + -2(2y + x) + y = 0
(x * 3 + y * 3) + -2(2y + x) + y = 0
(3x + 3y) + -2(2y + x) + y = 0

Reorder the terms:
3x + 3y + -2(x + 2y) + y = 0
3x + 3y + (x * -2 + 2y * -2) + y = 0
3x + 3y + (-2x + -4y) + y = 0

Reorder the terms:
3x + -2x + 3y + -4y + y = 0

Combine like terms: 3x + -2x = 1x
1x + 3y + -4y + y = 0

Combine like terms: 3y + -4y = -1y
1x + -1y + y = 0

Combine like terms: -1y + y = 0
1x + 0 = 0
1x = 0

Solving
1x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '1'.
x = 0

Simplifying
x = 0

See similar equations:

| 1+n/3=-6 | | 2x+8+2x=10+2x+12 | | 1.2+y=-8 | | 4x-5=6x-13 | | 5-(x+3)+3x+3(x+2)= | | -18+12-3= | | (9x+9)+(-12x+24)= | | 4(x+3)+(x+6)+2(x-3)= | | 160s+465(88-s)=19265 | | n^2+14n-95=0 | | 0=7x-28 | | (x-5i)(x+5i)=0 | | 2x+y-3x+4y-6+5y= | | 1/3(2x+9)=2/3x+3 | | 5x+20=15+10x | | a-16=2(3-a) | | 9y=18x-54 | | 2p+9-8p=3p-18 | | 3(x+2)=2(x+1)-5 | | 8y-6=4y-18 | | 3a+22=7a+14 | | 2n-8=6n-32 | | 2(2x+6)=5x+9 | | 16x+27=75 | | -18=6k+6(1+3k) | | 2n-8=6n-(-32) | | f-14=6f | | 4(x+3)-12=3(x-6) | | 4x^3-12x^2-64x+192=0 | | -12=5v+2+2v | | -3b+2b-3b=6 | | 7h-18=31 |

Equations solver categories